Factors for Developing the Professional Competence of Professional Teachers - Mustafoeva, Durdona Asilovna (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the development of professional competence of teachers of higher education, modernization of the system of professional development and retraining of higher education institutions, professional competence, the essence of its content, approaches of researchers to the development of professional competence of teachers of professional sciences, stages of professional competence development competency review, through which issues such as factors of professional competence development are highlighted. Keywords— , S , , ,